Fixed Point Theorems for Contractive Mappings in Complete G-Metric Spaces. (16th April 2009) - Mustafa, Zead; Sims, Brailey
Abstract : We prove some fixed point results for mappings satisfying various contractive conditions on CompleteG -metric Spaces. Also the Uniqueness of such fixed point are proved, as well as we showed these mappings areG -continuous on such fixed points.